Actinobacillus hominis osteomyelitis: First reported case in the English language medical literature. Issue 3 (10th June 2016) - O'Neill, Gavin; Ker, Andrew; Mohammed, Aslam; Karcher, Anne Marie
Abstract : Introduction: Actinobacillus hominis is currently a rarely reported pathogen. It has previously been associated with respiratory tract infections and bacteraemia in debilitated patients. However, under-reporting may occur due to misidentification by commonly used laboratory bacterial identification systems. This case is, to the best of our knowledge, the first reported case of A. hominis osteomyelitis in the English language medical literature. Case presentation: A 37-year-old male presented with a painful foot. He had no previous foot problems, history of injury or animal contact. Osteomyelitis was confirmed by magnetic resonance imaging (MRI), and blood cultures were positive for Gram-variable bacilli. The organism was identified initially as Pasteurella pneumotropica by the local routine diagnostic laboratory and as a Pasteurella species by the UK National Reference Laboratory (Colindale, London, UK), using standard operating procedures at the time. It was finally identified as an A. hominis using 16S rRNA gene sequence analysis. Difficulties in the accurate identification of this organism remain current, as other biochemical identification systems have also resulted in misidentifications. The patient refused admission and intravenous antibiotics. He was successfully treated using an 8-week course of oral ciprofloxacin and amoxicillin based on antibiotic disc susceptibility testing resulting in clinical, serological and radiological resolution. Conclusion: Laboratories should maintain a high index of suspicion for A. hominis as several commonly used bacterial identification systems may not accurately identify the organism. Colonial morphology and absence of animal contact should prompt consideration of this organism in appropriate clinical situations. Oral ciprofloxacin and amoxicillin treatment was successful in this case.